The use of metformin in the treatment of Intrahepatic cholestasis of pregnancy - Pawłowska, Paulina; Ozga-Stachurska, Alicja; Wójcik-Grudzień, Justyna; Rozenbajgier, Martyna (Journal of Education, Health and Sport, 2022)
Introduction: Intrahepatic cholestasis of pregnancy (ICP) is the most common pregnancy-related liver disease. It is characterized by persistent pruritus, usually occurring after 30 weeks of pregnancy, and by elevated levels of bile acids and transaminases, which decrease over the course of 2-3 weeks postpartum. [1,2]The occurrence of ICP in the mother may be associated with significant complications in the fetus, such as: preterm labor, intrauterine asphyxia, or sudden fetal death. Currently, the treatment of choice is ursodeoxycholic acid (UDCA).[2,6] Recently, it was observed that the administration of metformin in cases not responding to standard therapy improved lipid disorders in pregnant women. The aim of the study: The aim of the study is to present the possibility of using metformin in the treatment of ICP in pregnant women not responding to standard treatment and to present a clinical case.. Material and methods: The work is a review of the literature on the management of ICP and the use of metformin in the treatment of lipid metabolism disorders, as well as a brief case report of a patient with intrahepatic cholestasis of pregnancy. Description of the state of knowledge: Metformin is an oral antidiabetic drug belonging to the group of biguanides. However, the latest observations show that metformin also has a beneficial effect on the liver function and on the lipid metabolism in pregnant women. In these patients, the levels of bile acids and liver enzymes decreased after the use of metformin. Summary: The mechanism of action of metformin explaining its beneficial effect on the lipid metabolism in pregnant women with intrahepatic cholestasis is not fully understood.